2014
DOI: 10.1159/000362172
|View full text |Cite
|
Sign up to set email alerts
|

Trigeminal Neuralgia Related to Megadolichobasilar Artery Compression: A Prospective Series of Twenty-Nine Patients Treated with Gamma Knife Surgery, with More Than One Year of Follow-Up

Abstract: Background: Trigeminal neuralgia (TN) secondary to megadolichobasilar artery (MBA) compression is considerably difficult to manage surgically. Objective: This study aims to evaluate the safety/efficacy of Gamma Knife surgery (GKS) in this special group of patients. Methods: Between July 1992 and November 2010, 29 patients with >1 year of follow-up presenting with MBA compression were treated with GKS at Timone University Hospital. Radiosurgery was performed using a Gamma Knife (model B, C or Perfexion). A sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 46 publications
(83 reference statements)
0
11
0
Order By: Relevance
“…In their study, Park et al 97 concluded that there was no significant difference between patients with vertebrobasilar ectasia (VBE) and those without in terms of the rates of initial complete pain relief (p = 0.6), time to pain recurrence (p = 0.25), and postoperative sensory changes (p = 0.73); however, longterm results at 5 years were better in the patients without VBE (42% vs 10%). In the series by Tuleasca et al, 135 both initial pain relief and long-term pain control were better than in their general series, 114 with a low complication rate. In selected cases, RS can be a safe and valuable alternative for this particular anatomical condition.…”
Section: Neurovascular Conflict and Its Effect On Pain Reliefmentioning
confidence: 75%
See 2 more Smart Citations
“…In their study, Park et al 97 concluded that there was no significant difference between patients with vertebrobasilar ectasia (VBE) and those without in terms of the rates of initial complete pain relief (p = 0.6), time to pain recurrence (p = 0.25), and postoperative sensory changes (p = 0.73); however, longterm results at 5 years were better in the patients without VBE (42% vs 10%). In the series by Tuleasca et al, 135 both initial pain relief and long-term pain control were better than in their general series, 114 with a low complication rate. In selected cases, RS can be a safe and valuable alternative for this particular anatomical condition.…”
Section: Neurovascular Conflict and Its Effect On Pain Reliefmentioning
confidence: 75%
“…With the exception of 1 prospective study by Régis et al, 112 all other studies were retrospective. In addition to those studies selected for the systematic review, we separately discuss trials that considered MVD versus RS (4 studies); 73,92,94,107 eye lens dose (2); 70,81 CT only-based targeting (4); 7,71,96,140 anterior versus REZ target (3); 88,99,141 the relationship between focal enhancement of the trigeminal nerve and/or brainstem and outcome (3); 2,38,40 one versus two 4-mm isocenters (4); 4,26,32,106 one 4-mm isocenter versus concentric 4-and 8-mm isocenters (1); 54 the neurovascular conflict and its effect on pain relief (5); 14,30,85,120,122 major neurovascular conflict by the megadolichobasilar artery (3); 97,127,135 eventual vascular damage after RS (1); 78 QOL and patient satisfaction (6); 9,51,95,103,112,115 potential impact of radiation dose rate (3); 6,10,68 eventual radioprotective effects of medication (1); 33 effect of beam channel blocking, with a longer irradiated nerve and integral dose (2); 86,87 timing of RS from the onset of symptoms (1); 91 previous surgery versus no previous surgery (2); 34,35 GKS after previous surgery (3); 49,…”
Section: Reporting Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 497 patients had more than 1 year of follow-up. We excluded from our final analysis patients with TN secondary to multiple sclerosis, 37 megadolichobasilar artery compression, 39 or a second GKS treatment, 40 which are reputed to have more variable responses to radiosurgery and were beyond the scope of this study.…”
Section: Patientsmentioning
confidence: 99%
“…A total of 130 consecutive patients treated between May 1993 and September 2003, all evaluated according to our prospective protocol, were followed up for more than 7 years. Patients with TN secondary to multiple sclerosis [13] or megadolicho-basilar artery compression [14], or having had a second radiosurgery [15], reputed to have more variable responses, were excluded. The Ethics Committee of the Timone University Hospital (CPPRB 1) approved our study.…”
Section: Methodsmentioning
confidence: 99%